Perspectives On The Use Of Qiyas Between Imam Bukhari And Imam Syafie - M. Qamarulzaman M. Zani; Amran Abdul Halim; Azman Ab Rahman (Universiti Sains Islam Malaysia, 2024)
Journal of Fatwa Management and Research, Volume 29 Issue 3 Page (63–79)